Socio-legal Notes on the Scope of the Migrant Vote in Buenos Aires City - Penchaszadeh, Ana Paula (2022)
Since 1987, migrants residing in the city of Buenos Aires have had the right to participate in local elections. The city’s Electoral Code, approved in 2018 and applied for the first time in the 2021 local elections, changed the regime of voluntary registration in the electoral register to one of automatic registration. This change not only increased the number of foreigners authorized to cast the vote, but it was also accompanied by a significant growth in migrant electoral participation. This article projects an analysis at three different levels. Firstly, it addresses the historically determined relationship between nationality, residence and access to the political community, with special emphasis on the exercise of political rights by migrants in the Argentine context. Afterwards, it considers the legislative and institutional transformations that, since the entry into force of the new Electoral Code, have entailed a transformation of the political-electoral role of the migrant group in the city of Buenos Aires. Finally, it analyzes some of the effects of automatic registration on the electoral behavior of the migrant group, trying not to lose sight of the composition and internal dynamics of this population as possible explanatory patterns of its electoral behavior